2014
DOI: 10.1111/jsm.12405
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Patients with Polycystic Ovary Syndrome (PCOS): A Model-Based Study of Predictive Factors

Abstract: Introduction Understanding the factors that contribute to health-related quality of life (HRQOL) is critical for developing the most appropriate interventions for improving or maintaining the HRQOL in polycystic ovary syndrome (PCOS) patients. Aim This study sought to determine the most significant predictors of the HRQOL in patients with PCOS. Methods This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 48 publications
4
39
0
Order By: Relevance
“…We determined more significant changes in psychological component of quality of life compared to physical one in PCOS patients, similar to other scientists [5,9,10]. Problems with self-esteem, self-perception and sexual dysfunction are usually associated with PCOS [11]. Results of our study have demonstrated that persons of active reproductive age face greater challenges with increased body weight, metabolic changes than women in early reproductive age.…”
Section: Discussionsupporting
confidence: 68%
“…We determined more significant changes in psychological component of quality of life compared to physical one in PCOS patients, similar to other scientists [5,9,10]. Problems with self-esteem, self-perception and sexual dysfunction are usually associated with PCOS [11]. Results of our study have demonstrated that persons of active reproductive age face greater challenges with increased body weight, metabolic changes than women in early reproductive age.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, in Iranian culture infertility is a stigma and thus fertility is an important factor for family stability. It is argued that infertility in eastern culture might affect women more compared with women from western cultures [37]. Insecurity about fertility as well as distorted self-perception may contribute negatively to sexual satisfaction and sexual self-worth possibly by affecting self-esteem and female identity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in the field of measuring the quality of life of women with PCOS have concluded that the quality of life of these women is very low. On this basis many gynecology researchers emphasize that patients should receive knowledge about this disease and its associated problems and even suggest that routine screening for the diagnosis of psychiatric diseases should be conducted in this group and these women need to receive education and support (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%